Oro-pharyngeal and esophageal motility and dysmotility - Pandolfino, John E. (Henry Stewart Talks, 2011)
Oro-pharyngeal and oesophageal motility can be adequately evaluated using techniques incorporating high-resolution manometry and fluoroscopy, Major defects in neuromuscular control and function may lead to malnutrition, respiratory complications and a reduction in quality of life, Oro-pharyngeal and esophageal motor disorders are classified based on patterns of contractile function, Treatment of motility disorders are determined by manometric patterns of function, Update interview: New treatments for esophageal motility disorders, Update interview: Per Oral Endoscopic-(Esophageal) Myotomy (POEM) and treatment of achalasia, Update interview: Tailoring treatment for type III achalasia and jackhammer esophagus, Update interview: Mapping out areas of spasm or hypercontractility, Update interview: Anatomy is an important modulator of esophageal contractile activity, Update interview: Obstruction related to a stricture, hernia or post-surgical, Update interview: This is not a true primary motor abnormality and the obstruction should be addressed first, Update interview: Esophagogastric junction outflow obstruction (EGJOO) requires complementary testing, Update interview: Obstruction on esophagram and Functional lumen imaging probe (FLIP), Update interview: Gut-brain interplay in dysphagia
Updated at 2020/05/15